Investigation and Analysis of The Performance Characteristics of Horizontal Axis Wind Turbine Blade with Dimple By Using CFD - V. Madhanraj , E.Harish Reddy , S.Subhani Basha , K.G. Krishna Murthy , G.Bhanu Chandra , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Renewable energy can realize by the amount of energy which is continuously required for the present and future generation. Wind energy is one of the rapidly growing power producing technology in this world. Wind power is extracted from air flow using wind turbines to produce the electricity. Wind power is an alternative to burning fossils which is clean and doesn’t produce any greenhouse toxic and poisoned gases during its operation. The main idea of this project is to investigate and analyse the aerodynamic effects of dimples on the surface of the horizontal axis wind turbine blade. This investigation speaks about the increase in efficiency when the dimples are added on the blade surface of the wind turbine.